Mobile transitions to adulthood and soft skills of Polish and Lithuanian return migrants = Mobilne wchodzenie w dorosłość i kompetencje miękkie polskich i litewskich migrantów powrotnych - Grabowska, Izabela; Jastrzębowska, Agata (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The main aim of this article is to analyse the interplay between international migration, life events related to transition to adulthood and the acquisition of soft skills as a result of working and living abroad. The article is based on an online survey conducted in spring and summer 2020 among 740 Polish and Lithuanian return migrants from the UK who returned to Poland and Lithuania.
Keywords: mobile transitions to adulthood; soft skills; return migrants; mobilne wchodzenie w dorosłość; kompetencje miękkie; migranci powrotni